Chinese hackers steal Tibetan writer's online identity. (Tibetan Review: The Monthly Magazine on all Aspects of Tibet, 2008)
The article reports that Tibetan writer Tsering Woeser's online identity has been used by Chinese hackers. According to the author, the Skype account of Woeser was used in fraud and exchange messages to Woeser's contact to trick them and gain politically sensitive information. In addition, the author notes that the Red Hackers' Alliance, a government supported nationalist hackers, assumes responsibility in hacking all the online accounts of Woeser.